2021
DOI: 10.1364/ao.438530
|View full text |Cite
|
Sign up to set email alerts
|

Explosion wave and crack field of an eccentric decoupled charge

Abstract: To investigate the characteristics of the explosion damage from an eccentric decoupled charge, the rock-breaking mechanism of an eccentric decoupled charge is revealed from the perspectives of the explosion wave field and crack field through theoretical and experimental analyses. The ratio of the maximum to minimum pressure on an eccentric decoupled hole wall increases exponentially with an increase in the decoupling coefficient, but it does not change with a change in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Liu et al [31] developed and designed tensile and compressive damage models using the finite element method, and then assessed the influence of different initiation point positions on the solid medium destruction using an experimental bench. To study blast wave field, Zuo et al [32], [33] analyze characteristics of blast shock wave propagation and gaseous detonation products when a cylindrical charge is initiated at its end and center. They have found that range of medium destruction at each initiation mode is about five times of explosive cavity diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [31] developed and designed tensile and compressive damage models using the finite element method, and then assessed the influence of different initiation point positions on the solid medium destruction using an experimental bench. To study blast wave field, Zuo et al [32], [33] analyze characteristics of blast shock wave propagation and gaseous detonation products when a cylindrical charge is initiated at its end and center. They have found that range of medium destruction at each initiation mode is about five times of explosive cavity diameter.…”
Section: Introductionmentioning
confidence: 99%